A Practical Procedure for Pre-irrigation Soil Survey in Orissa - Mishra, D.P. (Journal of Soil and Water Conservation, 2022)
Availability of water is the most important factor for crop production. For assured and increased crop production it is essential to have a number of irrigation projects to supplement natural rainfall. This assumes great importance due to erratic nature of the mon-soon. However, it is erroneous to have the notion that if darns are constructed and sufficient water is supplied to the field the problem is solved. Infact sometimes irrigation may bring more problems than those already existed in the Pre-irrigation days. Poor drainage and high salt concentration lead to soil deterioration and poor crop growth. And copious irrigation would only aggravate such conditions. A soil survey of the ayacut area prior to the execution of the scheme is, therefore, helpful. To cite one example, in case of the proposed Gundlakama irrigation project in the district of Guntur examination of soils of the ayacut area revealed that while irrigation of the area on the north would be beneficial, the area on the south would not be so due to poor drainage and very high salt content of the soil. Consequently execution of the Gundalakama project was not recom-mended.